Sit and be fit : fibromyalgia workout [videorecording (DVD)] - Wilson, Mary Ann (Sit and Be Fit, 2005)
Activities in this balanced exercise and relaxation program are done sitting in a chair or standing beside the chair. The program is designed by Mary Ann Wilson, RN, to meet the special needs of senior citizens, arthritis sufferers, stroke patients and others needing slow, gentle movements.